Poročila - Metka Špes; Blaž Komac; Dejan Cigale; Nejc Bobovnik; Lea Rebernik; Jasna Sitar; Darko Ogrin; Tim Gregorčič; Jaka Grad; Lena Kropivšek; Sašo Stefanovski; Job Stopar; et al. (Dela, 2023)
Uvod v študij geografije